2019
DOI: 10.1149/2.0221914jes
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Nanostructured Electrocatalysts for Hydrogen Evolution in an Anion Exchange Membrane Lignin Electrolysis Cell

Abstract: The aim of this study is to quantify the hydrogen production rate in an anion exchange membrane (AEM) lignin electrolysis cell. Two non-precious and nanostructured metal and metal oxide electrocatalysts were developed and used as the anodic catalysts in a lignin electrolysis process. H 2 production rates, energy consumption rates and faradaic efficiency were measured using β-PbO 2 /MWNTs and Ni-Co/TiO 2 electrocatalysts as the anode, where electrochemical depolymerization of lignin occurs. Our results were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…45.6 ml h À 1 ) at the cathode in an anion exchange membrane (AEM) electrolysis cell, which reduced energy consumption by 20 % compared to commercial alkaline water electrolysis. [42] NiCo/TiO 2 as the anode electrocatalyst exhibited a similar effect. [43] Caravaca et al used polymer electrolyte membrane-based (PEM) reactors to perform the electrolysis of lignin-containing alkaline solutions in continuousflow mode for H 2 production with low electrical potentials (starting at ca.…”
Section: The Reactions In Direct Electrooxidation Of Ligninmentioning
confidence: 66%
See 2 more Smart Citations
“…45.6 ml h À 1 ) at the cathode in an anion exchange membrane (AEM) electrolysis cell, which reduced energy consumption by 20 % compared to commercial alkaline water electrolysis. [42] NiCo/TiO 2 as the anode electrocatalyst exhibited a similar effect. [43] Caravaca et al used polymer electrolyte membrane-based (PEM) reactors to perform the electrolysis of lignin-containing alkaline solutions in continuousflow mode for H 2 production with low electrical potentials (starting at ca.…”
Section: The Reactions In Direct Electrooxidation Of Ligninmentioning
confidence: 66%
“…Bateni et al loaded PbO 2 on MWCNTs to make a nanocomposite anode that showed superior catalytic activity and stability and enhanced lignin oxidation rates. [42] Furthermore, four IrO 2 -based MMO electrodes (Ti/SnO 2 À IrO 2 , Ti/RuO 2 À IrO 2 , Ti/Ta 2 O 5 À IrO 2 and Ti/TiO 2 À IrO 2 ) for lignin electrooxidation were fabricated by overlaying the binary metal oxides on pretreated Ti substrates. [55] The electrochemical studies revealed that: (i) the Ti/RuO 2 À IrO 2 electrode shows the highest stability and the highest activity for lignin depolymerization; (ii) the Ti/Ta 2 O 5 À IrO 2 electrode shows the best activity for oxygen evolution but worst activity for lignin depolymerization; (iii) the electrooxidation of lignin on all four IrO 2 -based electrode follows pseudo first-order kinetics.…”
Section: Dimensionally Stable Anodes (Dsas; Metal Oxide/mixed Metal Omentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing lignin concentration up to 50 gL À1 was found to increase the reaction rate. Simultaneously, Bateni, et al [141] studied the hydrogen production in an anion-exchange membrane reactor using b-PbO 2 /MWNT( multi-walled carbon nanotube) in comparison to the NaderiNasrabadi's Ni-Co/TiO 2 electrocatalyst. Polarization and chronoamperometric studies indicated that b-PbO 2 /MWNTshowedh ighers tability,a ctivity,a nd enhanced reaction rates towards lignin oxidation and hydrogen gas cogeneration compared to Ni-Co/TiO 2 .…”
Section: Electrochemical Degradation Of Lignin For Hydrogen Co-producmentioning
confidence: 99%
“…[141] They determined that higher initial lignin concentration (100 gL À1 )a nd higher anode catalyst loading (10 mg cm À2 )r esulted in improvedperformancef or lignin oxidation and hydrogen production and a2 0% improvement in energy efficiency when compared to commercial alkaline electrolyzers. [141]…”
Section: Electrochemical Degradation Of Lignin For Hydrogen Co-producmentioning
confidence: 99%